The efficacy of botulinum toxin A and sacral neuromodulation in the management of interstitial cystitis (IC)/bladder pain syndrome (BPS), what do we know? ICI‐RS 2017 think thank, Bristol. (24th January 2018) - Rahnama'i, Mohammad S.; Marcelissen, Tom; Apostolidis, Apostolos; Veit‐Rubin, Nikolaus; Schurch, Brigitte; Cardozo, Linda; Dmochowski, Roger
Abstract : Aims: This manuscript aims to address the evidence availale in the literature on the efficacy of Botulinum Toxin A (BoNT‐A) and sacral neuromodulation (SNM) in patients suffering from Interstitial Cystitis (IC)/BPS and propose further research to identify mechanisms of action and establish the clinical efficacy of either therapy. Methods: At the International Consultation on Incontinence‐Research Society (ICI‐RS) in 2017, a panel of Functional Urologists and Urogynaecologists participated in a Think Tank (TT) discussing the management of IC/BPS by BoNT‐A and SNM, using available data from both PubMed and Medicine literature searches. Results: The role of BoNT‐A and SNM in the treatment of IC/BPS are discussed and mechanisms of actions are proposed. Despite the available randomized trial data on the effect of intravesical BoNT‐A treatment on symptoms of IC/BPS, a consistent conclusion of a positive effect cannot be drawn at the moment, as the published studies are small and heterogeneous in design. There is substantive evidence for the positive effects of SNM on symptoms of IC/BPS patients however, during patient selection, it is important to distinguish the degree and the location of pain in order to tailor the best therapy to the right patients. Conclusions: Both intravesical BoNT‐A treatment and SNM have been shown to have positive effects in patients with IC/BPS. However, firm conclusions cannot yet be drawn. Patient‐reported outcomes and quality of life should be assessed in addition to urinary and pain symptoms. Since current treatments mainly focus on symptomatic relief, future research should also focus on clarifying the pathogenic mechanisms involved in IC/BPS.